(untitled) (Journal of Organizational Psychology, 2021)
We study the employability skills expected of accounting graduates in regional metropolitan areas, which may significantly differ from the diverse economies of large central metropolitan areas. We investigate the differences in technical and soft skills demanded by metropolitan areas in the state of Texas. We assess the differences in technical skills versus soft skills for 14 Metropolitan Statistical Areas (MSAs) and 12 Occupational in the State of Texas. We examine the job postings and find that Communication skills are in high demand irrespective of the size of the metropolitan area. Large metro areas have a higher demand for analytical and team/cooperative skills while Medium metro areas and Border cities have a higher demand for organizational, detail oriented/meticulous, and management skills. Although all areas show many similarities in the technical skills they demand, Medium metro areas and Border cities showed a demand for Bilingual skills. We find that the different economic needs should be addressed with a regional perspective.